Assessing size effects on the deformation of nanovoids in metallic materials. (1st March 2020) - Hure, J.; Barrioz, P.O.; Tanguy, B.
Graphical abstract: Abstract: An experimental methodology is developed to evaluate size effects in nanovoids deformation under macroscopic uniaxial stress loading conditions. Quantitative evaluation of voids deformation as a function of voids size shows both a crystallographic effect, albeit small compared to the scatter, and no evidence of size effects for voids diameter larger than 10 nm, while a slight effect is present for smaller voids. Critical assessment of the data in light of theoretical models indicates that these results may be compatible with the presence of a hardened layer at the void/matrix interface, which is illustrated through finite element simulations accounting for surface tension.